РИСКОВОЕ КАРТИРОВАНИЕ ЗАГРЯЗНЕНИЯ ОКРУЖАЮЩЕЙ СРЕДЫ ПРИ АВАРИИ НА НЕФТЕПРОВОДЕ - Балакай Л.А.; Дедова Т.В.; Миркаримова Б.М.; Закарин Э.А. (My University, 2006)
Выполнены расчеты и построены карты рисков для двух случаев гипотетической аварии на нефтепроводе. Авария на суше относится к магистральному нефтепроводу, причем предполагается возгорание пролитой нефти и соответствующее загрязнение атмосферы. Для случая аварии на нефтепроводе, проложенном по дну моря, рассчитываются риски загрязнения нефтью водного бассейна.

The problem of ecological risk mapping for possible accident on the land or seabed oil pipeline is considered. The developed methodology includes following steps: · to compose environment uncertainty model as the set of equally possible meteorological situations (each during 120 hours); · to calculate the pollutant transfer for all set of these meteorological situations; · to calculate the expectation value as risk criteria and to map of this risk distribution; · to calculate and to map the risk distribution indicated the exceeding of pollution sanitary norms. The calculations are carried out and results are represented as risk maps for two cases of hypothetical accidents on the oil pipeline. The first case concerns to the accident on the land oil pipeline. It is supposed that the oil mass spilled on the land, saturated it and ignited with pollution of atmosphere. The second case concerns to seabed oil pipeline. The accident led to generation of the oil slick and spreading it on sea surface.
Keywords: 504.05:62/69